Oxidative stress, inflammation, and muscle soreness in an 894-km relay trail run - Rowlands, D. S.; Pearce, E.; Aboud, A.; Gillen, J. B.; Gibala, M. J.; Donato, S.; Waddington, J. M.; Green, J. G.; Tarnopolsky, M. A. (European Journal of Applied Physiology, 2012)
We describe the effects of multi-day relay trail running on muscle soreness and damage, and systemic immune, inflammatory, and oxidative responses. 16 male and 4 female athletes ran 894 km in 47 stages over 95 h, with mean (SD) 6.4 (1.0) stages per athlete and 19.0 (1.7) km per stage. We observed post-pre run increases in serum creatine kinase (qualified effect size extremely large, p = 0.002), IL-6 (extremely large, p < 0.001), urinary 8-isoprostane/creatinine (extremely large, p = 0.04), TNF-a (large, p = 0.002), leukocyte count (very large, p < 0.0001) and neutrophil fraction (very large, p < 0.001); and reductions in hemoglobin (moderate, p < 0.001), hematocrit (moderate, p < 0.001), and lymphocyte fraction (trivial, p < 0.001). An increase in ORAC total antioxidant capacity (TAC, small, p = 0.3) and decrease in urinary 8-OHdG/creatinine (small, p = 0.1) were not statistically significant. During the run, muscle soreness was most frequent in the quadriceps. The threshold for muscle pain (pain-pressure algometry) in the vastus lateralis and gastrocnemius was lower post-run (small, p = 0.04 and 0.03). Average running speed was correlated with algometer pain and leukocyte count (large, r = 0.52), and TAC was correlated with IL-6 (very large, r = 0.76) and 8-isoprostane/creatinine (very large, r = -0.72). Multi-day stage-racing increases inflammation, lipid peroxidation, muscle damage and soreness without oxidative DNA damage. High TAC is associated with reduced exercise-induced lipid peroxidation, but is not related to immune response or muscle damage.